The effect of tip credits on earnings and employment in the US restaurant industry - William E. Even; David A. Macpherson (Institute for the Study of Labor (IZA), 2012)
According to federal law in 2012, employers can take a credit of up to 5.13 for tips received by workers in satisfying the minimum wage requirement of 7.25. This study uses interstate variation in laws regarding tip credits and minimum wages to identify the effects of reducing or eliminating the tip credit on employment and earnings in the U.S. restaurant industry. Using data from the Quarterly Census of Employment and Wages and the Current Population Survey, we find that a reduction in the tip credit increases weekly earnings but reduces employment in the full services restaurant industry and for tipped workers. The results are robust to controls for spatial heterogeneity in employment trends and are supported by a series of falsification tests.
Keywords: J30; J31; J38; 330; tip credit; minimum wage; tipped workers; cash wage; earnings; employment; Gastronomie; Mindestlohn; Trinkgeld; Tourismusberufe; Beschäftigungseffekt; USA